Inhibition of apricot polyphenol oxidase by combinations of plant proteases and ascorbic acid - Ala eddine Derardja; Matthias Pretzler; Ioannis Kampatsikas; Malika Barkat; Annette Rompel (Food Chemistry: X, 2019)
The present research investigates the long term inhibition of enzymatic browning by inactivating the polyphenol oxidase (PPO) of apricot, using combinations of plant proteases and ascorbic acid (AA). The selected proteases were able to inactivate PPO at pH 4.5, with the degree of inactivation proportional to incubation time and protease concentration. Papain was the most effective protease, with 50 μg completely inactivating PPO in less than one hour. AA prevented browning reactions that occur before or during PPO inactivation by protease. The combinations of AA/proteases were highly effective in vitro, where 2 mM AA/500 μg proteases inhibited PPO activity completely over 24 h. The combination of AA/proteases was also effective in vivo, as treated apricot purees preserved their color (p < 0.0001, compared to untreated samples after 10 days of storage). The results demonstrate that AA/proteases combinations constitute a promising practical anti-browning method with feasible application in the food industry. Keywords: Enzymatic browning, Polyphenol oxidase, Apricot, Plant proteases, Ascorbic acid